Problem Solving Ability Reviewed from Independent Learning at Social Media based Blended Learning - Fikriyah, Millatina; Zaenuri, Zaenuri; Nur Cahyono, Adi (Universitas Negeri Semarang, 2021)
This research aims to analyze the problem-solving ability of learners reviewed from their independent learning ability in blended learning assisted by social media. The population of this research consisted of X grade of Public Senior High School 6 Semarang Municipality, in the academic year 2019/2020. The sample was selected by random cluster sampling. The sample groups were X Science 1 as the experimental group while X Science 4 as the control group. This research is mixed-method research. The techniques of collecting quantitative data were the creative thinking ability test and the independent learning ability questionnaire. The technique of collecting qualitative data was done by interview based on the independent learning ability questionnaire and the problem-solving ability test result. The data was processed by a z-test, one-sample t-test, and an independent t-test. The findings showed that the problem-solving ability was reviewed by the independent learning ability realized into high, moderate, and low variety categories. It was shown by 6 students with high independent learning ability had 3 students with excellent problem-solving ability and 3 students with fair problem-solving ability. From 24 students with moderate independent learning ability, there were 10 students with excellent problem-solving abilitys, 12 students with fair problem-solving abilitys, and 3 students with low problem-solving abilitys. From 6 students with low independent learning ability, 1 student had excellent problem-solving abilitys, 3 students with fair problem-solving abilitys, and 2 students with sufficient problem-solving abilitys.